eCM 2012
DOI: 10.22203/ecm.v023a32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibrin on osteogenic differentiation and VEGF expression of bone marrow stromal cells in mineralised scaffolds: a three-dimensional analysis

Abstract: The aim of the present study was to test the hypothesis that a fibrin matrix enhances the osteogenic differentiation and expression of vascular endothelial growth factor (VEGF) by human bone marrow stromal cells (hBMSCs) seeded into mineralised scaffolds. Porous calcium carbonate scaffolds were droplet seeded with hBMSCs using a matrix containing 3 % fibrinogen and cultured for 3 weeks. Seeded scaffolds without the fibrin matrix served as controls. The scaffolds were evaluated, using undecalcified thick sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…This bioactive factor/scaffold has disadvantages when used as scaffolds, such as low rigidity that can produce shrinkage of scaffols and rapid degradation that would not permit proper bone regeneration. Therefore, other proposals suggest the use of fibrin as an adjunt element for sustaining osteogenic capacity of stem cells in mineralized scaffolds [26]. PRGF has also been considered as a natural scaffold [19] with advantages such as flexibility, non toxic, no immune reaction, complete resorption [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…This bioactive factor/scaffold has disadvantages when used as scaffolds, such as low rigidity that can produce shrinkage of scaffols and rapid degradation that would not permit proper bone regeneration. Therefore, other proposals suggest the use of fibrin as an adjunt element for sustaining osteogenic capacity of stem cells in mineralized scaffolds [26]. PRGF has also been considered as a natural scaffold [19] with advantages such as flexibility, non toxic, no immune reaction, complete resorption [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…However, the maximum level of expression of OC and VEGF in hBMSCs did not increase through the use of fibrin. 111 Kneser et al 42 immobilized osteogenic cells in fibrin and seeded them into a processed bovine cancellous bone (PBCB) matrix. Later, scaffolds with and without cells were implanted into a rat calvarial defect.…”
Section: 109mentioning
confidence: 99%
“…The gel degradation added variability to protein expression data, and highlighted the improved stability of the construct with a scaffold. This has been noted in the literature, where it has been demonstrated that scaffolds and fibrin gels stimulate the greatest healing response when used together [11,12,37].…”
Section: Relative Contributions Of Architecture and Fibrin Gelmentioning
confidence: 71%
“…With the addition of fibrin gels to scaffolds, tissue engineering outcomes, such as in vitro blood vessel formation and osteogenic differentiation, have been shown to improve [11,12]. While the advantage of adding fibrin to tissue engineering constructs is clear, the effects of combining fibrin gel and architectural cues has, to our knowledge, never been examined.…”
Section: Introductionmentioning
confidence: 99%